Adsorption of copper(II) from aqueous solution by Beidellite - Oncel, M. S. (Springer, 2008)
Beidellite was used as an adsorbent for the removal of copper ions from aqueous solutions. Batch mode studies were carried out by varying initial copper (II) concentrations (50-500 mg/l), initial pH (2.0-5.0), adsorbent particle size (0.095-0.890 mm) and temperature (293-333 K). A contact time of 60 min was required to reach equilibrium. Adsorption of the metal ion was highly pH dependent and the optimum pH for the removal was 5.0 at which the removal was maximum (25.3 mg/g). The result showed that the amount adsorbed of the metal ion increased with increasing initial copper (II) concentration and contact time. Three adsorption kinetic models, the pseudo first-order, second-order and intraparticle diffusion were applied to experimental data to predict the adsorption rate constants. A comparison of kinetic models on the overall adsorption rate showed that metal ion/adsorbent system was best described by the pseudo second-order rate model. The adsorption capacity (Q (o)) calculated from the Langmuir isotherm was 71.07 mg/g for at pH 5.0, 293 K for the particle size of 0.095-0.890 mm. The experimental data yielded excellent fits with Langmuir isotherm equation. Different thermodynamic parameters viz., changes in standard free energy, enthalpy and entropy were evaluated and it was found that the reaction was spontaneous and endothermic in nature.
Keywords: Beidellite; copper removal; adsorption; adsorption isotherm; adsorption kinetic